Learning Written Communicative Skills in UOC Engineering Curricula: A Virtual University Initiative and Its Future Development - Marco-Galindo, M Jesús; Macau-Nadal, Rafael; Pastor-Collado, J Antoni (2010 IEEE Transforming Engineering Education: Creating Interdisciplinary Skills for Complex Global Environments, 2010)
Essays, reports and projects are often difficult to read and understand, usually not because their content is complex but because they are badly written and presented, showing that our students (the professional or academic computing engineers of the future) lack the ability to write clearly and precisely. To address the problem, we decided to take on the challenge of improving the students' communicative skills by including communicative competence in the Computing Engineering curricula at the Universitat Oberta de Catalunya (UOC), the Open (virtual) University of Catalonia. We designed a specific subject to complement the normal curricula: "Communicative Competence for Computing Professionals", which was introduced in the 2004/05 academic year. This paper describes our experience of this initiative. After introducing the subject design, we report on the results obtained over these years and examine its strengths and limitations. Finally, building upon this analysis, we consider how to support and enhance the learning of communicative skills in the future.